The Effect of External Pressure, Financial Stability, and Financial Target on Financial Reporting Fraud - Divian, Dinda Tri Novianty; Subiyanto, Bambang; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to obtain empirical evidence on the influence of external pressure, financial stability, and financial targets on financial reporting fraud in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020. The population in this study is manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange through the www.idx.co.id website during the period 2016-2020. The samples in this study are 14 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020 which have been selected by purposive sampling method. The type of data used in this study is secondary data. Data collection techniques and tools in this study used documentation methods and literature studies. The data analysis method used is multiple linear regression analysis. The results obtained in this study show that external pressure and financial targets have a significant negative effect on financial statement fraud. Meanwhile, financial stability does not have a significant effect on financial statement fraud.